LANGUAGE POWER IN COURTROOM: THE USE OF PERSUASIVE FEATURES IN OPENING STATEMENT - Supardi, Supardi (Universitas Pendidikan Indonesia, 2016)
Language is a powerful tool for communication that many people can use for persuasion. In the courtroom, for example, lawyers use language to persuade the jury that their client is right and should win the case. Though many studies have discussed this issue, how language becomes powerful in the trial opening statement remains underresearched. For this reason, this study addresses a textual analysis on the patterns of language used by a lawyer in the opening statement. Such analysis provides a solid understanding of how language can become persuasive in the courtroom. The data source of this study were taken from the text of the Opening Statement by O.J. Simpson’s Defense Lawyer (Walraven, 1995). Although this text does not seem new regarding the publication date and some articles have discussed this, it is a seminal work, which can represent the construction of language power in the opening statment. To analyse the data collected from this text, the researcher adopted the model developed by Miles and Huberman (1994). This study firstly explores the overview of opening stetement persuasive features. In addition, it presents the finding and discussion which reveal that language power in the courtroom can be reflected in some persuasive features such as metaphor, repetition, and rhetorical question as found in the text of Opening Statements by O.J. Simpson’s Defense Lawyer.